2021
DOI: 10.1097/mot.0000000000000904
|View full text |Cite
|
Sign up to set email alerts
|

Access to liver transplantation for minority populations in the United States

Abstract: Purpose of review Racial disparities in access to liver transplantation have been known since the National Transplant Act of 1980. Since the inception of the Final Rule in 2000, the United Network of Organ Sharing has sought to ensure the equitable distribution of donor livers. Despite several measures aimed to improve access for vulnerable populations, disparities in outcomes are still prevalent throughout the liver transplant (LT) evaluation, while on the waitlist, and after liver transplantation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“… 1 Women, racial and ethnic minority populations, and patients with public insurance, low educational level, and low income all have lower rates of listing for organ transplant, higher rates of waitlist mortality, and lower rates of transplant from living donors. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Transplantation is a highly complex, often regionalized system of care that requires completion of a multi-step conditional selection process. Inequities in access to transplantation likely result from a combination of the complexity of the transplant selection process and individual social conditions (eg, health literacy, employment, access to transportation) that burden patients as they navigate the process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 1 Women, racial and ethnic minority populations, and patients with public insurance, low educational level, and low income all have lower rates of listing for organ transplant, higher rates of waitlist mortality, and lower rates of transplant from living donors. 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 Transplantation is a highly complex, often regionalized system of care that requires completion of a multi-step conditional selection process. Inequities in access to transplantation likely result from a combination of the complexity of the transplant selection process and individual social conditions (eg, health literacy, employment, access to transportation) that burden patients as they navigate the process.…”
Section: Introductionmentioning
confidence: 99%
“…Inequities in access to organ transplant are longstanding, having been described for over 20 years . Women, racial and ethnic minority populations, and patients with public insurance, low educational level, and low income all have lower rates of listing for organ transplant, higher rates of waitlist mortality, and lower rates of transplant from living donors . Transplantation is a highly complex, often regionalized system of care that requires completion of a multi-step conditional selection process.…”
Section: Introductionmentioning
confidence: 99%
“…[1] Existing disparities within the previous policy are well documented, such as the underrepresentation of non-Hispanic Black and Hispanic patients on the liver transplant (LT) waitlist and higher mortality for minority populations on the waitlist. [2] Concerns were raised that the AC policy would differentially harm racial and ethnic minorities by shifting transplants from areas of higher-minority populations to lower-minority populations, thereby exacerbating existing disparities in access to LT. Since the implementation of the AC policy, studies have demonstrated several positive (eg, increased transplantation of high MELD patients) and negative (eg, increased travel and costs) consequences.…”
mentioning
confidence: 99%
“…We are willing to take their organs, but not willing to transplant-surely a social justice issue. 13 Another long-standing issue has to do with the buying of organs, having individuals travel to countries where they are engaged in purchasing organs despite the long-term deleterious effects to the donor's health. However, there are economic benefits that should be taken into consideration: first to the institution and second to the individual donor.…”
mentioning
confidence: 99%